THE IMPLEMENTATION OF QUIZIZZ MEDIA IN LEARNING BASIC ENGLISH VOCABULARY - Kolanus, Dominique; Olii, Sanerita; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of the research is to describe the process of implementation of Quizizz in learning English basic vocabulary. This research was qualitative research, consisting of data reduction, data presentation, and drawing and verifying conclusions (Miles & Huberman, 1992). The population of this study was students of SD Inpres 4/82 Pandu and samples were taken from one class of five classes consisting of around 20 students. Data was collected starting from observations, instructions for using Quizizz media as well as exercises, interviews, and documentation. The result explained that Media Quizizz as a tool for students to learn basic English vocabulary has a positive impact, namely it can help students use computers, acquire and recognize new English vocabulary. In accordance with the research objective of explaining the implementation of Quizizz media in learning basic English vocabulary, students are able to use Quizizz media well, remember the correct answers, and gain knowledge in increasing fifth grade students’ basic English vocabulary.